MAKNA PUISI POHON PERADABAN KARYA DINULLAH RAYES KAJIAN SEMIOTIKA RIFFATERRE - Diana, Jumianti (Jurnal Pena Indonesia, 2018)
The article examines Dinullah Rayes's poem "Pohon Peradaban" taken from the anthology of his poem entitled Bulan di Pucuk Embun (2011). The poem is one of Dinullah Rayes's poems which uses many natural symbols, such as trees, roots, moon, sun, leaves, flowers, maggots and so on. This study uses descriptive qualitative research methods and uses the semiotic theory proposed by Riffaterre, that is by doing heuristic reading, hermeneutic or retroactive reading and determining the matrix of the poem. The results of the study show that we must keep this friendly culture belonging to our nation so that it does not disappear. We must also maintain character and friendship in order to stay alive in peace.Â Â